Strong regional transport of volatile organic compounds (VOCs) during wintertime in Shanghai megacity of China. (1st January 2021) - Liu, Yuehui; Wang, Hongli; Jing, Shengao; Peng, Yarong; Gao, Yaqin; Yan, Rusha; Wang, Qian; Lou, Shengrong; Cheng, Tiantao; Huang, Cheng
Abstract: Measurements of volatile organic compounds (VOCs) were performed as well as other pollutants in Shanghai in winter. The whole measurements were classified into three types of periods, including particulate pollution episodes (PPE), VOC pollution episodes (VPE), and relatively clean periods based on the pollution characteristics. Of these types, PPE have the highest fine particulate matter (PM2.5 ) mass concentrations and second-highest VOC concentrations, mainly impacted by the regional transport of aged air masses from the northwest. VPE generally concern long-lasting high concentrations of VOCs under stagnant atmospheric conditions due to the accumulation of local emissions. Five sources of VOCs were identified by the positive matrix factorization (PMF) model, and furthermore, the analysis of VOCs concentration weighted trajectory (CWT) was employed to investigate the potential source region and even to validate the source identification to some extent. As a result, VOCs in Shanghai in winter were mainly from solvent usage (23.9%), vehicle emissions mixed with some petrochemical emissions (24.7%), natural gas and background (23.6%), combustion-related to regional transport (22.1%), and secondary formation (5.7%). The regional transport, usually with large combustion sources, played more important roles (41.9%) in VOCs during PPE compared to VPE and clean periods. The contribution of local emissions like vehicle exhaust and petrochemical emissions increased during VPE compared to PPE and clean periods. Clean periods have low PM2.5 and low VOC concentrations, with a large contribution from the regional background. The present study highlighted the regional transport of VOCs should be taken into account for policymakers when making the city scale controlling measures. Highlights: Meteorological conditions strongly influenced VOCs characteristics in winter. PPE and VPE were two kinds of typical pollution episodes in winter. Regional transport-related combustion from the northwest played important roles during PPE. Local emissions dominated the increase of VOCs during VPE.